2020
DOI: 10.3126/jbpkihs.v3i1.30322
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mild-Cognitive-Impairment and Depression among Elderly Clients in Selected Wards of Baraha Municipality: A Cross-Sectional Study

Abstract: Introduction: Mild-Cognitive-Impairment (MCI) is an intermediate state between normal cognitive ageing and dementia. Identification of MCI is thought to be crucial to early intervention. Objectives: To assess Mild-Cognitive-Impairment and Depression among elderly clients and to find out the associations between Mild-Cognitive-Impairment and Depression and socio-demographic variables. Methods: A descriptive, cross-sectional study design was adopted. A total of 115 elderly clients who fulfilled the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The prevalence revealed by the Memory First Aid Informant Questionnaire/CSI-D for informants instrument was similar to that found in a recent study in Nepal, which revealed that 75% of older adults have dementia symptoms using the Cognitive Impairment Test (CIT) tool in residential care homes [6]. About 93.0% was screened for mild cognitive impairment with 115 individuals (60 years and older) using the Montreal Cognitive Assessment (MoCA) [7]. However, the prevalence of cognitive impairment revealed in the current investigation is much higher than found in a recent systematic review focused on global prevalence, using results from 80 studies which revealed a range of 5-41% [22]; and in another national study from China, which found a prevalence rate of 22.2% [23].…”
Section: The Prevalence Of Cognitive Impairment or Risk Of Dementia I...supporting
confidence: 78%
See 1 more Smart Citation
“…The prevalence revealed by the Memory First Aid Informant Questionnaire/CSI-D for informants instrument was similar to that found in a recent study in Nepal, which revealed that 75% of older adults have dementia symptoms using the Cognitive Impairment Test (CIT) tool in residential care homes [6]. About 93.0% was screened for mild cognitive impairment with 115 individuals (60 years and older) using the Montreal Cognitive Assessment (MoCA) [7]. However, the prevalence of cognitive impairment revealed in the current investigation is much higher than found in a recent systematic review focused on global prevalence, using results from 80 studies which revealed a range of 5-41% [22]; and in another national study from China, which found a prevalence rate of 22.2% [23].…”
Section: The Prevalence Of Cognitive Impairment or Risk Of Dementia I...supporting
confidence: 78%
“…It is estimated that over 135,000 people in Nepal may live with dementia, with almost 50% of the population over age of 60 years having some form of memory-related problems [5]. In Nepal, a recent study has determined that nearly 75% of older people living in residential homes in urban areas have dementia symptoms [6] and 93% of older people aged 60 years and above have mild cognitive impairment in one municipality [7]. The situation is compounded in Nepal by a tendency to dismiss symptoms of dementia as part of the normal ageing process, with a general lack of awareness of the symptoms of dementia in the general population [8].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of dementia has predominantly been based on studies conducted in hospitals, and very few from communities 55 and OAHs 56 . The results from these studies shows the prevalence rates range from 3.9% to 28% which probably might be because of the different tools and different cutoffs used to ascertain the diagnosis (Table 2).…”
Section: Resultsmentioning
confidence: 99%